Strategic Implementation of Key Principles in Tourism Transportation Communication: Catalyst for Advancing Tourism Development in Bogor City, West Java - Wihardi, Doddy; Pratikto, Riyodina Ganefsri; Waluyo, Nadira Ardanti (Institute of Computer Science (IOCS), 2024)
Many places in Indonesia have developed into attractive tourist destinations for visitors. One of the tourist destinations that has recently gained rapid development and attention from tourists is the city of Bogor. Bogor has evolved into a highly sought-after destination for both domestic and international tourists. However, the biggest challenge for the development of a tourist destination lies in the availability of well-connected public transportation and easily accessible information about public transportation for tourists. As Bogor has grown into a tourist destination, the researcher aims to understand how the availability of public transportation and the dissemination of information are handled for tourists visiting the city. This study will be grounded in the perspective of tourism communication, utilizing the concept of tourism transportation communication. The research methodology involves a case study with interviews and literature review as data sources. Through this research, it is hoped to provide insights and understanding of transportation policies in Bogor and how information about public transportation can be effectively communicated to tourists. The results of the study indicate that the development of the tourism sector in Bogor has been accompanied by the city government's commitment to providing comfortable public transportation and comprehensive information for tourists utilizing public transportation